Felix Meagher interviewed by Rob Willis in the Rob and Olya Willis folklore collection - Meagher, Felix; Willis, Rob, 1944- (2007)
Folkloric recording. Felix Meagher talks about his education; moving to Melbourne; his parents' background; his siblings; his musical influences from mother's family; learning music; his high school life; writing and producing musicals; playing in bands; his education; making a living out of music; his contact with folk music; Cobbers; Christy Cooney; fiddle playing; importance of music teaching; Jamie McKew; Ronald Stevenson; Percy Grainger; his thesis on folk music; John Meredith; Baz Luhrmann; background to 'Music 81 in Victoria' program; working in the Northern Territory; the play 'Pure Merino Fandango'; settling down with wife in Melbourne; creation of band 'Bushwahzee'; needing stable income; other bush bands; his expectations of being a full time musician; creating and marketing the show 'Bush Cabaret'; Port Fairy Folk Festival; dance content of band Bushwahzee; Brian Moran.his future direction; Bushwahzee in 1989; Maity Swallow; philosophy of Lake School; Dennis O'Keefe; his involvement in the Lake School; Martin Hayes; 'Spud Poets'; 'Koroit' area; judges of poetry; the legends of the Lake School.
Recorded by Olya Willis.
Accompanying photographs.
Recorded on July 3, 2007 at Balnarring, Vic.
Digital master available
Felix Meagher born 1955 in Darwin, is a performer and composer. He has worked with well known film producer Baz Luhrmann on several of his projects. Currently, he continues his career in music with the professional band 'Bushwahazee'. The band mainly performs in schools.
Timed summary and uncorrected transcript (typescript, 66 leaves) available.
Keywords: Meagher, Felix -- Interviews; Folk musicians -- Victoria -- Interviews; Folk music groups -- Victoria; Music camps -- Victoria; Folk music -- Victoria; Musicians